2014
DOI: 10.3389/fimmu.2014.00271
|View full text |Cite
|
Sign up to set email alerts
|

HP-1γ Controls High-Affinity Antibody Response to T-Dependent Antigens

Abstract: In vitro observations suggest a role for the mouse heterochromatin protein 1γ (HP-1γ) in the immune system. However, it has not been shown if and how HP-1γ contributes to immunity in vivo. Here we show that in mice, HP-1γ positively regulates the germinal center reaction and high-affinity antibody response to thymus (T)-dependent antigens by limiting the size of CD8+ regulatory T-cell (Treg) compartment without affecting progenitor B- or T-cell-development. Moreover, HP-1γ does not control cell proliferation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Recently, we showed that in C57BL/6 mice, haploinsufficiency of Cbx3 /HP1γ impairs the lymphoid-tissue germinal center (GC) reaction and high-affinity antibody response against a thymus (T)-dependent antigen (Ag) conjugated to chicken gamma globulin (NP-CGG) 15 . The effects were CD8 + -T-cell-intrinsic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed that in C57BL/6 mice, haploinsufficiency of Cbx3 /HP1γ impairs the lymphoid-tissue germinal center (GC) reaction and high-affinity antibody response against a thymus (T)-dependent antigen (Ag) conjugated to chicken gamma globulin (NP-CGG) 15 . The effects were CD8 + -T-cell-intrinsic.…”
Section: Resultsmentioning
confidence: 99%
“…Homozygous germline deletion of Cbx3 /HP1γ in mice causes embryonic lethality 13 14 . Previously we have shown that Cbx3 /HP1γ haploinsufficiency is sufficient to regulate the high-affinity antibody response to protein antigens 15 . However, it has not been determined how Cbx3 /HP1γ does so.…”
mentioning
confidence: 98%
“…Our recent studies suggest that such an approach is attainable. We show that by targeting the histone reader Cbx3 /HP1γ, we can enhance the tumor killing capacity of effector CD8 + T cells ( 69 , 70 ). As a result, adoptive transfer of Cbx3 /HP1γ-deficient CD8 + effector T cells alone into wild type (wt) tumor-bearing mice greatly reduces NB growth.…”
Section: Adoptive T-cell Therapy (Act)mentioning
confidence: 92%
“…The mammalian HP1 family consists of three members, HP1α, HP1β, and HP1γ, coded by Cbx5 , Cbx1, and Cbx3 genes, respectively . Their localization in the cell nucleus is different despite their high amino acid sequence similarity suggesting that each HP1 has unique functions as seen in gene knockout studies . In neural tissues, HP1β and HP1γ are involved in neural development.…”
Section: Introductionmentioning
confidence: 99%
“…15 Their localization in the cell nucleus is different despite their high amino acid sequence similarity 28,29 suggesting that each HP1 has unique functions as seen in gene knockout studies. [30][31][32][33][34][35] In neural tissues, HP1β and HP1γ are involved in neural development. Mutations in HP1β cause defects in proliferation of nerve cell precursors accompanied by increased genome instability, reflecting the function of HP1β to stabilize heterochromatin.…”
Section: Introductionmentioning
confidence: 99%